Metallothionein concentrations in a population of Patella aspera: variation with size - Bebianno, Maria João (2020)
The determination of metallothionein (MT) concentrations in species with different feeding habits is important from the ecotoxicological point of view because it provides a better understanding of the role of these proteins in metal uptake pathways. The main objective was study the variation of NIT and metal (Cd, Cu and Zn) concentrations with size and weight in the limpets Patella aspera. In addition investigate the relationship between NIT and metal concentrations in limpets from different metal load environments - of the south coast of Portugal with the aim to use MT in P aspera as a biomarker of metal exposure. MT concentrations in the whole soft tissues of R aspera increased with size and weight while metals decrease with size and weight. NIT concentrations showed no significant relationship with Cd or Cu concentrations in the limpets from the South Portuguese Coast. However, a negative exponential relationship detected between MT and Zn concentrations suggest that Zn bound to NIT might be displaced by Cd or Cu ions. The ability of limpets to store both Cd and Cu bound to NIT may be responsible for the tolerance of this species to contaminated environments. The relationship between MT concentrations and Zn indicates that NIT seems to play a minor role in binding Zn in Patella species.